Analysis of Effect of Perceived Ease of use and Usefulness on Consumer Interest use of Banking Products Farmer Card in Mataram (Global Journal of Management and Business Research, 2020)
Agriculture is an important sector for the nation of Indonesia. The current phenomenon in Indonesia is still going on the scarcity of fertilizers, especially subsidized fertilizer which has always been a problem every year. The government has tried various strategies to address shortages of fertilizer subsidized by Tani Card Program with the hope to increase the GDP of the agriculture sector Mataram City. The objectives of this study were (1) To examine the effect of perceived ease of use against the interest of consumers using Katu Tani. (2) To examine the effect of the perception of the benefit of the interest of consumers using Katu Tani. method of research is associative with the shape of a causal relationship. The population in this study is a farmer in the district card users Sekarbela Kota Mataram amounted to 148 people. Tool collection Data is a questionnaire, which contains statements related to the problems studied. To determine the response of respondents to the variables assessed, used a Likert scale analysis tools. Analysis of data using Multiple linear regression analysis, t-test, and test the coefficient of determination (R²). conclusions of research that can be taken are:(1) There is a significant effect of Perceived ease of use on Consumer Interests in Sub Sekarbela Mataram.
Keywords: perceived ease of use; perceived usefulness; consumer interests